Peran Pendidik Dalam Upaya Deradikalisasi Paham Keagamaan - Fikriansyah, Fikriansyah (Tarbawi : Jurnal Ilmu Pendidikan, 2019)
Abstract The radicalism of religious (Islamic) ideology which continues to spread in every circle must receive more attention by doing efforts both preventive, persuasive, repressive and curative. Efforts to de-radicalization in a persuasive way can be done through education. In the world of education, the central figure is an educator. Educators can provide understanding that can accept any differences that exist in Indonesia. as the core of the elimination of radicalism in the world of education is an educator must have a tolerant and pluralist understanding to be able to become an agent of piece. Using literature studies, and case analysis in the field, this paper will provide an conceptual illustration of how a teacher plays a role in the effort to deradicalize religious ideas.